Pulsed versus Continuous Tones for Evaluating the Loudness of Tinnitus - Henry, James A.; Meikle, Mary B. (Journal of the American Academy of Audiology, 1999)
Loudness balance techniques are commonly employed to match the loudness of tinnitus using either pulsed or continuous tones; however, it is not known whether the tone duration affects the observed loudness matches. In this study, hearing thresholds and tinnitus loudness matches were measured in 26 subjects with chronic tinnitus using both pulsed and continuous tones. Subjects' thresholds and loudness matches were determined at 11 frequencies between 0.5 and 10 kHz. No significant differences were found between pulsed versus continuous measures, either for thresholds or for loudness matches. There were, however, nine subjects (34.5% of the group) who showed relatively large differences (≥10 dB) at one or more test frequencies. These "outlier" values did not show systematic trends; some were positive, some negative. In conclusion, studies employing group data appear to be comparable if group sizes are sufficiently large (e.g., ≥ 25 subjects). Studies employing smaller numbers of subjects may, however, be vulnerable to potential positive or negative biases introduced by one or more outliers.Abbreviations: ANOVA = analysis of variance
Keywords: Continuous; high-frequency hearing; intermittent; loudness; pulsed; tinnitus